The Effect of Counseling Using Dental Spinning Wheel Media on Knowledge and Oral Hygiene of Mentally Impaired Children in SLB Negeri Cineam, Tasikmalaya Regency - Indharni, Peby Liana (Politeknik Kesehatan Kementerian Kesehatan Semarang, 2025)
Problem statement: Children with intellectual disabilities have a very high risk of dental disease. The cause of the occurrence is lack of awareness of maintaining dental and oral hygiene, so efforts are made to maintain dental and oral hygiene through counseling, selection of appropriate methods and media. Counseling using dental spinning wheel media is a method that attracts the attention of children with intellectual disabilitie. Purpose: To determine the effect of counseling using dental spinning wheel media on the knowledge and oral hygiene of children with intellectual disabilities in SLB Negeri Cineam, Tasikamalaya regency. Method: Using quasi-research method (quasy experiment) with one group pretest and posttest design. The sample technique used was a total sampling of 13 SDLB students, 11 SMPLB students and 10 SMALB students with a total of 34 students. Research data was obtained by providing knowledge questionnaires and Hygiene Index (HI) examinations. Data analysis using Wilcoxon statistical test using SPSS application. Results: The results of statistical tests that there is an influence of counseling using dental spinning wheel media, which shows the results (p 0.005), then there is a significant influence between counseling using dental spinning wheel media with knowledge and dental and oral hygiene of children with intellectual disabilities. Conclusion: There is an influence of dental spinning wheel media on knowledge and dental and oral hygiene in children with intellectual disabilities in SLB Negeri Cineam.